Mobile Virtual Work A New Paradigm? - Andriessen, J.H. Erik; Vartiainen, Matti (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Dear Reader This is a book about mobile virtual work. It aims at clarifying the basic concepts and showing present practices and future challenges. The roots of the book are in the collaboration of few European practitioners and - searchers, who met each other under the umbrella of the Swedish SALTSA programme (see next page) in January 2002 in Stockholm. The group was first called 'ICT, Mobility and Work Organisation' but redefined itself quickly as 'Mobile Virtual Cooperative Work' group. The change of the name reflects the development of reasoning in the group. We could not find much material on mobile work, certainly not systematic studies, - though a growing interest in mobile technologies and services could be found. Practices of telework and virtual organizations were better known, but we were convinced that the combination with mobile work was so- thing different and new. Our main target became to understand what it was all about. The next step was an expert meeting in October 2004 at Rånäs Castle again in Sweden. A wider group of experts was invited to present their views on mobile virtual work and ideas about book chapters from different perspectives of working life. Some of the expertise could be found through the network of the AMI@Work family created by the New Working En- ronments unit of the European Commission's Information Society Dir- torate-General. Also close collaboration was developed with the related MOSAIC program.